PANGGILAN SECARA ELEKTRONIK DALAM PROSEDUR SIPIL, DALAM UPAYA PENYELESAIAN WARISAN KOLONIAL - bagus sujatmikp (Judex Laguens, 2024)
The court summon is the first spearhead of the entire trial process, especially for the civil cases. Court summon has an essential role, even the summon process may decide the legitimation of a trial that conducted by the judge. The court summon is conducted in order to inform the parties when they should appear before the judge. It becomes important due to its impact to the parties’ life fate, either its right over goods or its legal status on a family. Therefore, the laws shall ensure that every person shall know whenever their rights being challenged before the court. In civil cases the court summon is regulated under Article 390 HIR (718 RBg), which is one of its kind is known as public summon. The legal basis to conduct the public summon in last 170 years has not been changed, only public summon in certain case that amended, such as in divorce case. Even then, the change does not really change the summoning process, the summoning still conducted by using a announcing paper that put in the government building and announcing through conventional media mass such as newspaper, radio or television. However nowadays, this kind of media has been left by the people, their popularity has been stolen by the internet like youtube, facebook, Instagram and etc. The Supreme Court (Mahkamah Agung, hereafter as “MA”) shall adapt to this era, MA shall re-innovate the way public summon conducted in last 170 years, by using the innovation of the 21th century which is the “internet”, by using the “Electronic Public Summon”.